2012
DOI: 10.1155/2012/716056
|View full text |Cite
|
Sign up to set email alerts
|

Reduced TCA Flux in Diabetic Myotubes: Determined by Single Defects?

Abstract: The diabetic phenotype is complex, requiring elucidation of key initiating defects. Diabetic myotubes express a primary reduced tricarboxylic acid (TCA) cycle flux but at present it is unclear in which part of the TCA cycle the defect is localised. In order to localise the defect we studied ATP production in isolated mitochondria from substrates entering the TCA cycle at various points. ATP production was measured by luminescence with or without concomitant ATP utilisation by hexokinase in mitochondria isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…They have demonstrated a preserved metabolic phenotype (eg, insulin responsiveness, glucose and lipid metabolism, ATP synthesis) in some of these human muscle cells. For instance, myotubes derived from obese individuals with T2D retain the impaired mitochondrial function that was observed in vivo (61,62). Consistent with these findings, data from Hulver and colleagues (65), along with some of our own work, have demonstrated that myotubes of nondiabetic individuals with severe obesity and those from obese T2D individuals retained an abnormal lipid partitioning similar to that observed in their muscle tissue (65,66).…”
Section: In Vitro Studiessupporting
confidence: 67%
See 1 more Smart Citation
“…They have demonstrated a preserved metabolic phenotype (eg, insulin responsiveness, glucose and lipid metabolism, ATP synthesis) in some of these human muscle cells. For instance, myotubes derived from obese individuals with T2D retain the impaired mitochondrial function that was observed in vivo (61,62). Consistent with these findings, data from Hulver and colleagues (65), along with some of our own work, have demonstrated that myotubes of nondiabetic individuals with severe obesity and those from obese T2D individuals retained an abnormal lipid partitioning similar to that observed in their muscle tissue (65,66).…”
Section: In Vitro Studiessupporting
confidence: 67%
“…Gaster and colleagues (61)(62)(63)(64) have performed several studies in human primary myotubes from various clinical phenotypes including leanness, obesity, insulin resistance, and T2D. They have demonstrated a preserved metabolic phenotype (eg, insulin responsiveness, glucose and lipid metabolism, ATP synthesis) in some of these human muscle cells.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Moreover, we found no significant differences in mitochondrial mass in myotubes established from lean, obese and obese T2D subjects (day 8) (148,152,152,158). The TCA cycle flux is reduced in diabetic myotubes (70,159), and this reduction cannot be attributed to a single TCA defect, as shown by us (159). In relation to this, we previously showed that day 8 diabetic myotubes exhibited a 14% reduction in basal CS activity compared to lean myotubes, indicating a mild TCA cycle impairment (130).…”
Section: Myotubes Established From T2d Subjects At Baselinementioning
confidence: 68%
“…We (Gaster et al) (68,70,84,111,148,152,152,158,158,159,161) found that day 8 diabetic myotubes express impaired insulin-stimulated glucose uptake, glycogen synthesis and glucose oxidation; impaired complete lipid oxidation; and reduced mitochondrial OXPHOS. In addition to the hyperphosphorylation of GS despite normal GSK3 activity and the reduced sensitivity of GS to the allosteric activator G6P under insulin stimulation, the primary abnormalities that occur at the transcriptional and protein levels are unknown.…”
Section: Insulin Resistance In Vitro and Its Characteristicsmentioning
confidence: 99%
“…And reduced TCA cycle flux in model group were observed according to the level of malic acid (FC = 0.656), succinic acid (FC = 0.792), fumaric acid (FC = 0.761), citric acid (FC = 0.812) when compared with normal group. The inhibition by high levels of NADH without ATP may lead to unmatched rate of citric acid cycle to meet energy demand [49]. In addition, the reason for suppressed TCA cycle in model group may be due to non-availability of oxaloacetate as it is channeled towards glucose production.…”
Section: Discussionmentioning
confidence: 99%